Dihydropyrimidinase Like 2 Promotes Bladder Cancer Progression via Pyruvate Kinase M2-Induced Aerobic Glycolysis and Epithelial–Mesenchymal Transition - Zou, Jun; Huang, Ruiyan; Chen, Yanfei; Huang, Xiaoping; Li, Huajun; Liang, Peng; Chen, Shan (Frontiers in Cell and Developmental Biology, 2021)
Background: Aerobic glycolysis and epidermal–mesenchymal transition (EMT) play key roles in the development of bladder cancer. This study aimed to investigate the function and the underlying mechanism of dihydropyrimidinase like 2 (DPYSL2) in bladder cancer progression. Methods: The expression pattern of DPYSL2 in bladder cancer and the correlation of DPYSL2 expression with clinicopathological characteristics of bladder cancer patients were analyzed using the data from different databases and tissue microarray. Gain- and loss-of-function assays were performed to explore the role of DPYSL2 in bladder cancer progression in vitro and in mice. Proteomic analysis was performed to identify the interacting partner of DPYSL2 in bladder cancer cells. Findings: The results showed that DPYSL2 expression was upregulated in bladder cancer tissue compared with adjacent normal bladder tissue and in more aggressive cancer stages compared with lower stages. DPYSL2 promoted malignant behavior of bladder cancer cells in vitro, as well as tumor growth and distant metastasis in mice. Mechanistically, DPYSL2 interacted with pyruvate kinase M2 (PKM2) and promoted the conversion of PKM2 tetramers to PKM2 dimers. Knockdown of PKM2 completely blocked DPYSL2-induced enhancement of the malignant behavior, glucose uptake, lactic acid production, and epithelial-mesenchymal transition in bladder cancer cells. Interpretation: In conclusion, the results suggest that DPYSL2 promotes aerobic glycolysis and EMT in bladder cancer via PKM2, serving as a potential therapeutic target for bladder cancer treatment.